Parking characteristics of multi-level parking facilities at berjaya Megamall, Kuantan - Nur Syazana, Khazili (2016)
This project is a researched about Parking Characteristics of Multi-level Parking Facilities in Berjaya Megamall, Kuantan. In case study, a method of study has been done, which is key-in the data collected from the authorities into the microsoft excel to get the duration in and out of each vehicle. The data collection have been key-in from starting operation of the day till Berjaya Megamall closed. So, from the data collected, the results and analysis were obtained which are, duration of parking, accumulation, parking turn-over (PTO), index parking (PI), and average of parking duration. Besides that, data were collected on weekends and weekdays during salary week and salary week. As the result, the highest parking demand is 06/02/2016 (Saturday) and followed by 27/02/2016 (Saturday) with values of 186 vehicles per hour and 157 vehicles per hour respectively. Next, from data analysis, the maximum parking accumulation is on 06/02/2016 (Saturday) and followed by 27/02/2016 (Saturday) with values of 411 vehicles and 343 vehicles respectively which is less than the parking capacity provided. Thus, there will be less traffic congestion at the parking spaces. Then, for non-salary week an average of parking duration at Berjaya Megamall on weekday shows the highest time which is on 09/02/2016 (Tuesday) with 1 hour 55 minutes, while for salary week, the highest time shows on weekend, 27/02/2016 (Saturday) with 1 hour and 48 minutes. As conclusion, parking bays at Berjaya Megamall, Kuantan were sufficient on both weekends and weekdays during salary weeks and non-salary weeks.